Tough customer - Brown, Sandra, 1948- (New York : Simon & Schuster, 2010)
Entreated by his former lover, Caroline, to help protect her daughter from a depraved man who has been stalking her, staff investigator Dodge Hanley teams up with a small-town sheriff and enlists methods from his own shady past to find answers.
Keywords: Stalkers -- Texas -- Fiction; Private investigators -- Texas -- Fiction; Houston (Tex.) -- Fiction; Suspense fiction